Pharmacokinetics and Monte Carlo Simulation of Meropenem in Critically Ill Adult Patients Receiving Extracorporeal Membrane Oxygenation - Lee, Jae Ha; Lee, Dong-Hwan; Kim, Jin Soo; Jung, Won-Beom; Heo, Woon; Kim, Yong Kyun; Kim, Se Hun; No, Tae-Hoon; Jo, Kyeong Min; Ko, Junghae; Lee, Ho Young; Jun, Kyung Ran; et al. (Frontiers in Pharmacology, 2021)
Objectives: There have been few clinical studies of ECMO-related alterations of the PK of meropenem and conflicting results were reported. This study investigated the pharmacokinetics (PK) of meropenem in critically ill adult patients receiving extracorporeal membrane oxygenation (ECMO) and used Monte Carlo simulations to determine appropriate dosage regimens. Methods: After a single 0.5 or 1 g dose of meropenem, 7 blood samples were drawn. A population PK model was developed using nonlinear mixed-effects modeling. The probability of target attainment was evaluated using Monte Carlo simulation. The following treatment targets were evaluated: the cumulative percentage of time during which the free drug concentration exceeds the minimum inhibitory concentration of at least 40% (40% fT>MIC), 100% fT>MIC, and 100% fT>4xMIC. Results: Meropenem PK were adequately described by a two-compartment model, in which creatinine clearance and ECMO flow rate were significant covariates of total clearance and central volume of distribution, respectively. The Monte Carlo simulation predicted appropriate meropenem dosage regimens. For a patient with a creatinine clearance of 50-130 ml/min, standard regimen of 1 g q8h by i.v. infusion over 0.5 h was optimal when a MIC was 4 mg/L and a target was 40% fT>MIC. However, the standard regimen did not attain more aggressive target of 100% fT>MIC or 100% fT>4xMIC¬. Conclusion: The population PK model of meropenem for patients on ECMO was successfully developed with a two-compartment model. ECMO patients exhibit similar PK with patients without ECMO. If more aggressive targets than 40% fT>MIC are adopted, dose increase may be needed.